Corporate tax harmonisation in Europe: A guide to the debate - Stephen Bond; Lucy Chennells; Michael P. Devereux; Malcolm Gammie; Edward Troup (Institute for Fiscal Studies (IFS), 2000)
Despite a long history of reports and initiatives on the harmonisation of corporate income taxes within the European Union, the 15 EU countries still operate their own national corporate income taxes, with only limited co-ordination between them. However, the increasing integration of economic activity is placing greater pressures on these corporate income taxes, as the companies whose profits are being taxed operate increasingly across national borders, both within Europe and beyond. Tax differentials may also be assuming greater importance in company decision-making, as other differences between countries within the EU diminish a trend highlighted by the adoption of a single currency within the Euro zone.
Keywords: 330